Sexual self-schema and sexual aggression of male readers of Lad Magazines - Aspero, Maris Pylene P.
This study was conducted to find out the impact of reading lad magazines on the sexual self-schema, and sexual aggression of men. One hundred men of fifty readers and fifty non-readers of lad magazines, from male domintaed insttitution, 18-30 years old served as participants of this study. A survey was conducted and four (4) instruments were used to measure the readership, sexual self-schema, and sexual aggression of man. The design of this study was correlational. To show relationship between variables, data were analyzzed using the pearson -r correlational statistics. The results of this research show that readership of lad magazines is associated with high sexual self-schema in the study sample and the likelihood of being sexually aggressive in comparison to non-readers. Men learned information regarding sex through lad magazines. These magazines also present women in a sexually arousing manner through their pictures and articles. Men's lifestyle was also affected by their readership of lad magazines.